Design And Development Of A Baby Sleep Monitoring System Based On Internet Of Things (Iot) - Irawan, Bambang; Yulhendri, Yulhendri; Kartini, Kartini; Anwar, Nizirwan; Tjahjojo, Budi; Sundari Meganingrum, Alpa (Publisher Cv. Inara, 2022)
A baby's condition during sleep is a condition that requires intense attention directly from the parents. The quality and quantity of baby sleep are very much affected by the conditions and setting of the environment where the baby sleeps, including the baby's space for movement, room temperature, light intensity, sound/noise, and humidity of the room. Keeping the quality of the baby's sleep is very important both for the baby and for parents. The Design and Development of a Baby Sleep Monitoring System Based on the Internet of Things (IoT) aim to help parents monitor their baby while sleeping and optimize the quality of baby's sleep by monitoring the conditions of the baby's bedroom environment without being present in person. Parents can monitor their baby's condition while sleeping by getting alerts to their smartphone if the conditions exceed the threshold of the ideal limits received from the IoT sensors, like sound sensor, movement sensor, temperature, and humidity sensor. Therefore parents can feel serenely in doing their daily activities, and the baby still gets theappropriate sleep needs.